In situ common garden assays demonstrate increased defense against natural fouling in non-native populations of the red seaweed Gracilaria vermiculophylla. - Wang, Shasha; Weinberger, Florian; Xiao, Luyang; Nakaoka, Masahiro; Wang, Gaoge; Krueger-Hadfield, Stacy A; Sotka, Erik E; Bian, Dapeng; Lenz, Mark (PANGAEA, 2016)
The susceptibility of native and non-native populations of the red alga Gracilaria vermiculophylla to fouling was compared in common garden experiments. Native and non-native algae were enclosed into dialysis membrane tubes, and the tubes were exposed to natural fouling. Fouling on the outside of the tubes was mediated by chemical compounds excreted by G. vermiculophylla that diffused through the membranes. Fouling pressure was significantly higher in the Kiel Fjord (non-native range) than in Akkeshi Bay (native range), but, at both sites, tubes containing non-native G. vermiculophylla were less fouled than those with native conspecifics. This is the first in situ evidence that susceptibility to fouling differs between native and non-native populations of an aquatic organism. The technique of enclosing organisms into dialysis tubes represents a simple, efficient and accurate way to test chemical antifouling defenses and could possibly be applied to other organisms.
In-situ-common-garden-assays demonstrate increased chemical defense against natural fouling in non-native populations of an aquatic organism